Efficient Hogel-Based Hologram Synthesis Method for Holographic Stereogram Printing - Erkhembaatar Dashdavaa; Anar Khuderchuluun; Hui-Ying Wu; Young-Tae Lim; Chang-Won Shin; Hoonjong Kang; Seok-Hee Jeon; Nam Kim (Applied Sciences, 2020)
With the development of the holographic printer, printing synthetic hologram requires smaller holographic element (hogel) size to improve spatial resolution of the reconstruction. On the contrary, a larger hogel size affords higher angular resolution, but it leads to a lower lateral resolution and there exists a trade-off problem. In this paper, a hologram synthesis method based on three-dimensional (3D) rendering of computer-generated holographic stereogram (HS) is proposed to limit the spatial-angular trade-off problem. The perspectives of the 3D scene are captured by re-centering the camera method and transformed into parallax-related images by a proposed pixel re-arrangement algorithm for holographic printing. Unlike the conventional approaches, the proposed algorithm not only improves the angular resolution of the reconstruction while maintaining the hogel size fixed, but also keeps the spatial resolution without degradation. The effectiveness of the proposed method is verified by numerical simulation and an optical experiment.